Transparent moisture absorbing film
Patent Information
- Application Number
- JP2020170626
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-10-08
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2040-10-08
AI Technical Summary
【0011】 本発明によれば、製造時に失活せず、かつブロッキングが抑制された、透明吸湿フィルムを提供することができる。
Smart Images

Figure 0007607429000002 
Figure 0007607429000003 
Figure 0007607429000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a transparent moisture-absorbing film. [Background technology]
[0002] In the field of packaging materials, moisture-absorbing films containing zeolite as a moisture absorbent are sometimes used. Also, films having transparency and moisture absorption properties are sometimes used as films for use in the fields of medicines, electronic parts, precision machinery, etc.
[0003] For example, Patent Document 1 discloses a moisture-absorbing resin composition that contains a zeolite having an average particle size D50 of 300 nm or less, an ester compound, and a thermoplastic resin, and that has a haze of 25% or more and 80% or less when measured on a film having a thickness of 100 μm before moisture absorption according to JIS K 7105. Patent Document 1 also discloses a moisture-absorbing film using this resin composition, and a moisture-absorbing laminate having this moisture-absorbing film between an outer skin layer and an inner skin layer.
[0004] Patent Document 2 discloses a transparent laminate for a blister pack, which comprises a first barrier film, a second barrier film, and an absorbent film in this order.
[0005] The film described in Patent Document 3 has extremely high transparency and is useful as a sealing film for organic electroluminescence (EL) displays.
[0006] Methods for producing nano-sized zeolite are described in Patent Documents 4 and 5. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2020 / 085445 [Patent Document 2] JP 2019-150987 A [Patent Document 3] JP 2018-100390 A [Patent Document 4] JP 2011-246292 A [Patent Document 5] JP 2013-49602 A Summary of the Invention [Problem to be solved by the invention]
[0008] When an attempt was made to produce a transparent laminate having a transparent moisture absorbing layer by simply incorporating the absorbent film of Patent Document 1 into the transparent laminate of Patent Document 2, the moisture absorbing layer was sometimes inactivated during the production of the transparent laminate. Furthermore, when this laminate was stored, the laminates sometimes stuck to each other (blocking).
[0009] Therefore, the present invention provides a transparent moisture-absorbing film that is not deactivated during production and in which blocking is suppressed. [Means for solving the problem]
[0010] As a result of intensive research, the present inventors have found that the above problems can be solved by the following means, and have completed the present invention. That is, the present invention is as follows: A transparent moisture-absorbing layer containing a thermoplastic resin and a moisture absorbent, and a first skin layer and a second skin layer laminated on the surface of the transparent moisture-absorbing layer, having The moisture absorbent has an average particle size of 1 μm or less as measured by a dynamic light scattering method; and The first and second skin layers each contain a cyclic olefin polymer. Transparent moisture absorbing film. <Aspect 2> The transparent moisture-absorbing film according to aspect 1, wherein the thermoplastic resin is a polyethylene-based resin. <Aspect 3> The transparent moisture-absorbing film according to aspect 2, wherein the thermoplastic resin is an ethylene-vinyl acetate copolymer. Aspect 4: The transparent moisture absorbing film according to any one of Aspects 1 to 3, wherein the moisture absorbent is a zeolite having an average particle size D50 of 300 nm or less. Aspect 5: The transparent moisture-absorbing film according to any one of aspects 1 to 4, wherein the transparent moisture-absorbing layer further contains an ester compound having an HLB value of 5 or less. Aspect 6: The transparent moisture-absorbing film according to aspect 5, wherein the content of the ester compound is 2.0 to 15.0% by mass based on the total mass of the transparent moisture-absorbing layer. <Aspect 7> The transparent moisture-absorbing film according to aspect 5 or 6, wherein the ester compound is a monoester of an alkylene glycol having 2 to 6 carbon atoms and a fatty acid having 15 to 24 carbon atoms. Aspect 8: Transparent barrier substrate layer, and The transparent moisture-absorbing film according to any one of aspects 1 to 7, which is laminated on the transparent barrier substrate layer. A laminate for a blister container, comprising: <Aspect 9> Contents, A blister container comprising the laminate for a blister container according to embodiment 8 and having a pocket; and a lid material attached to the blister container, thereby sealing the contents. A blister pack containing the contents. Effect of the Invention
[0011] According to the present invention, it is possible to provide a transparent moisture-absorbing film which is not deactivated during production and in which blocking is suppressed. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a cross-sectional side view of a transparent moisture-absorbing film of the present invention. [Diagram 2] FIG. 2 is a side cross-sectional view of the laminate for blister containers of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Transparent moisture absorbing film As shown in FIG. 1, the transparent moisture-absorbing film 10 of the present invention is A transparent moisture-absorbing layer 12 containing a thermoplastic resin and a moisture-absorbing agent; and First and second skin layers 14, 14' are laminated on the surfaces of the transparent moisture-absorbing layer, respectively. having The moisture absorbent has an average particle size of 1 μm or less as measured by a dynamic light scattering method; and Both the first and second skin layers 14, 14' contain a cyclic olefin polymer.
[0014] Here, in the present invention, "transparent" means that, for example, when the transparent moisture-absorbing film of the present invention is used as a packaging material and contents having visible information such as letters are sealed in this packaging material, the transparent moisture-absorbing film is sufficiently transparent to visually recognize the information through the transparent moisture-absorbing film. Specifically, "transparent" means, for example, a total light transmittance of 50% or more, 60% or more, 70% or more, 75% or more, 80% or more, 85% or more, 90% or more, 95% or more, or 100%, and a haze value of 25% or less, 20% or less, 15% or less, or 10% or less.
[0015] Here, the total light transmittance can be measured in accordance with JIS K 7361, and the haze value can be measured in accordance with JIS K 7136.
[0016] Moisture absorbents with small average particle sizes, particularly the specific zeolite mentioned in Patent Document 1, can provide transparency to the moisture absorbing layer. On the other hand, such moisture absorbents have a large surface area per unit mass, and therefore may be deactivated when mixed with a resin to form a moisture absorbing film.
[0017] In addition, when a moisture absorbing film is prepared using such a moisture absorbing agent and then stored, adjacent moisture absorbing films may stick to each other, resulting in blocking. In addition, when an ester compound for dispersing the moisture absorbing agent is added to the transparent moisture absorbing layer, this blocking occurs more significantly.
[0018] In response to this, the present inventors have found that the above-mentioned configuration makes it possible to provide a transparent moisture-absorbing film that is not deactivated during production and in which blocking is suppressed.
[0019] Each component of the present invention will now be described.
[0020] <Transparent moisture absorption layer> The transparent moisture absorbing layer contains a thermoplastic resin and a moisture absorbing agent.
[0021] From the viewpoint of dispersibility, it is preferable that the transparent moisture absorbing layer further contains an ester compound having an HLB value of not more than 5. On the other hand, when the transparent moisture absorbing layer contains this ester compound, blocking is likely to occur, and therefore the above-mentioned configuration of the present invention is useful.
[0022] The melt flow rate of the resin composition constituting the transparent moisture absorbing layer, measured in accordance with JIS K7210 under conditions of a temperature of 190°C and a load of 21.18N, is 0.3g / 10min or more and 30g / 10min or less. This makes it relatively easy to form the film by the T-die method or the inflation method, thereby facilitating the production of the transparent moisture absorbing layer. This melt flow rate may be 0.5g / 10min or more, 1.0g / 10min or more, 3.0g / 10min or more, or 5.0g / 10min or more, and may be 20g / 10min or less, 15g / 10min or less, 10g / 10min or less, 8.0g / 10min or less, or 5.0g / 10min or less. For example, this melt flow rate may be 0.5g / 10min or more and 10g / 10min or less.
[0023] The haze of the resin composition constituting the transparent moisture absorbing layer, when made into a film having a thickness of 100 μm before absorbing moisture and measured according to JIS K7136, is preferably 25% or less, and may be 20% or less, or 15% or less. For example, the haze may be 3% or more and 25% or less, or 5% or more and 20% or less. If it is within such a range, the film can be given a transparency that allows the inside to be clearly confirmed when used as a packaging container or the like.
[0024] The transparent moisture absorbing layer may or may not contain oxides (excluding zeolite) of one or more elements selected from Al, Si, Ti, and Zr having an average particle size D50 of 100 nm or less. The content of such oxides may be, for example, 5 mass % or less, 3 mass % or less, 1 mass % or less, or 0 mass %.
[0025] (thermoplastic resin) The thermoplastic resin constituting the moisture absorbing layer may be a polyolefin resin, a vinyl polymer, a polyester, a polyamide non-cyclic olefin polymer, or a cyclic olefin polymer.
[0026] Polyolefins include cyclic olefin-based polymers and non-cyclic olefin-based polymers.
[0027] Cyclic olefin-based polymers are polymers having cyclic olefin moieties. More specifically, reference is made below with respect to the skin layer.
[0028] The non-cyclic olefin polymer is a polymer that does not have a cyclic olefin moiety. Examples of the non-cyclic olefin polymer include polyethylene resins and polypropylene resins that do not have a cyclic olefin moiety.
[0029] In this specification, a polyethylene-based resin refers to a resin that contains 30 mol% or more, 40 mol% or more, 50 mol% or more, 60 mol% or more, 70 mol% or more, or 80 mol% or more of repeating units of ethylene groups in the main chain of the polymer, and is selected from the group consisting of, for example, low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), medium-density polyethylene (MDPE), high-density polyethylene (HDPE), ethylene-acrylic acid copolymer (EAA), ethylene-methacrylic acid copolymer (EMAA), ethylene-ethyl acrylate copolymer (EEA), ethylene-methyl acrylate copolymer (EMA), ethylene-vinyl acetate copolymer (EVA), carboxylic acid-modified polyethylene, carboxylic acid-modified ethylene-vinyl acetate copolymer, derivatives thereof, and mixtures thereof.
[0030] In this specification, a polypropylene-based resin refers to a resin containing 30 mol% or more, 40 mol% or more, 50 mol% or more, 60 mol% or more, 70 mol% or more, or 80 mol% or more of repeating units of propylene groups in the main chain of the polymer, and examples thereof include polypropylene (PP) homopolymer, random polypropylene (random PP), block polypropylene (block PP), chlorinated polypropylene, carboxylic acid-modified polypropylene, derivatives thereof, and mixtures thereof.
[0031] An example of the vinyl polymer is polyvinyl chloride (PVC).
[0032] Examples of polyester include polyethylene terephthalate (PET) and polybutylene terephthalate.
[0033] Examples of polyamides include nylons such as Nylon (registered trademark) 6 and Nylon MXD6.
[0034] As the thermoplastic resin, it is preferable to use a polyethylene-based resin, in particular a polyethylene-based resin containing a polar group such as a carboxylic acid group or a carboxylic acid ester group and an ethylene unit, from the viewpoint of the affinity between the zeolite and the ester compound.
[0035] Examples of polyethylene resins containing a polar group and an ethylene unit include ethylene-acrylic acid copolymer (EAA), ethylene-methacrylic acid copolymer (EMAA), ethylene-ethyl acrylate copolymer (EEA), ethylene-methyl acrylate copolymer (EMA), ethylene-vinyl acetate copolymer (EVA), carboxylic acid-modified polyethylene, and carboxylic acid-modified ethylene-vinyl acetate copolymer. In particular, the use of ethylene-vinyl acetate copolymer (EVA) is particularly preferred from the viewpoint of affinity between the zeolite and the ester compound.
[0036] The vinyl acetate content in the ethylene-vinyl acetate copolymer may be 10% by mass or more, 15% by mass or more, 20% by mass or more, 25% by mass or more, or 30% by mass or more, and may be 60% by mass or less, 55% by mass or less, 50% by mass or less, 45% by mass or less, or 40% by mass or less. The vinyl acetate content in the ethylene-vinyl acetate copolymer may be, for example, 5% by mass or more and 50% by mass or less, or 20% by mass or more and 40% by mass or less.
[0037] (Moisture absorbent) The moisture absorbent has an average particle diameter D50 of 1 μm or less as measured by dynamic light scattering. Examples of the moisture absorbent include physical moisture absorbents such as zeolite and silica gel, and chemical moisture absorbents such as calcium oxide, magnesium sulfate, calcium chloride, calcium oxide, and aluminum oxide.
[0038] Here, the average particle diameter D50 means a particle diameter at 50% of the cumulative value in the particle size distribution based on the number of randomly selected 100 particles measured along the major axis using a scanning electron microscope (SEM). The average particle diameter D50 of the moisture absorbent is 1 μm or less, 800 nm or less, 500 nm or less, or 300 nm or less, more preferably 100 nm or less, from the viewpoint of imparting transparency to the composition. The average particle diameter D50 of the moisture absorbent may be 300 nm or less, 250 nm or less, 200 nm or less, 150 nm or less, 130 nm or less, 100 nm or less, 80 nm or less, 70 nm or less, 60 nm or less, or 50 nm or less. The average particle diameter D50 of the moisture absorbent may be 5 nm or more, 10 nm or more, 20 nm or more, or 30 nm or more. For example, the average particle diameter D50 of the moisture absorbent may be 5 nm or more to 100 nm or less, or 20 nm or more to 80 nm or less.
[0039] The value of the atomic ratio of Si to Al (Si / Al) in the zeolite is arbitrary and may be, for example, 1 or more, 2 or more, 3 or more, 5 or more, 10 or more, or 15 or more, and may be, for example, 80 or less, 60 or less, 50 or less, 40 or less, or 30 or less.
[0040] The zeolite used in the present invention is preferably hydrophilic from the viewpoint of hygroscopicity, and it is particularly preferable to use Na-A type zeolite.
[0041] The zeolite used in the present invention can be produced, for example, by the methods described in Patent Documents 4 and 5. Such zeolites may be used after adjusting the bulk density as described in Patent Document 3.
[0042] The zeolite can be obtained, for example, by dispersing a raw material zeolite represented by the following formula (1) in an aqueous solution containing a silicate or aluminosilicate represented by the following formula (2) and recrystallizing the resulting mixture. aM 1 2O bSiO2 Al2O3 cMeO (1) {In formula (1), M 1represents an alkali metal atom, a hydrogen atom, or an ammonium ion, Me represents an alkaline earth metal ion atom, a is 0.01 to 1, b is 1 to 80, and c is 0 to 1.} dM 2 2O eAl2O3 fSiO2 gH2O (2) {In formula (2), the ratio d / g is 0.00035 to 0.02000, the ratio e / g is 0 to 0.00025, and f / g is 0.0001 to 0.025.}
[0043] In the above formula (1), b may be, for example, 2 to 60 or 20 to 80. c may be, for example, 0.01 to 1. In the above formula (2), the ratio d / g may be, for example, 0.003 to 0.010. The ratio e / g may be, for example, 0 or 0.000003 to 0.000250. The ratio f / g may be, for example, 0.0001 to 0.0160 or 0.006 to 0.025.
[0044] The raw material zeolite of the above formula (1) is, for example, NaSiAlO4, NaSi 12 AlO 26 , NH4Si 19 AlO 40 Examples of the silicate of the above formula (2) that can be used include 0.292Na2O·hSiO2·55.5H2O (h=0.400, 0.650, 0.800, or 1.00), iNa2O·0.650SiO2·55.5H2O (i=0.165 or 0.55), etc. Examples of the aluminosilicate of the above formula (2) that can be used include 405Na2O·jAl2O3·kSiO2·29,900H2O ((j,k)=(1,23), (1,51), (2,23), or (2,51)), etc.
[0045] The zeolite obtained as described above may be subjected to ion exchange or pulverization, or both, before use.
[0046] The content of zeolite in the transparent moisture absorbing layer is 3.0% by mass or more and 45% by mass or less, and may be 5% by mass or more, 10% by mass or more, 20% by mass or more, 30% by mass or more, 35% by mass or more, or 40% by mass or more, and may be 40% by mass or less, or 35% by mass or less. For example, the content of zeolite may be 10% by mass or more and 45% by mass or less, or 30% by mass or more and 45% by mass or less.
[0047] (Ester compounds) The transparent moisture absorbing layer contains an ester compound having an HLB value of not more than 5. The ester compound may be a compound used as an emulsifier or the like, and enables mixing of the zeolite used in the present invention with the thermoplastic resin.
[0048] The HLB value is an index of hydrophilicity or lipophilicity. An HLB value of 5 or less of an ester compound means that the ester compound has high lipophilicity, and is in the range where it can be used, for example, as a defoamer or an emulsifier for emulsions.
[0049] The HLB value of the ester compound may be 4.5 or less, 4.0 or less, or 3.5 or less, or may be 2.0 or more, 2.5 or more, or 3.0 or more. For example, the HLB value of the ester compound may be 2.0 or more and 5.0 or less, or 2.5 or more and 4.5 or less.
[0050] The ester compound is, for example, a monoester compound of a polyhydric alcohol and a fatty acid. The polyhydric alcohol may be, for example, glycerin, alkylene glycol, etc. The fatty acid may be, for example, a saturated or unsaturated fatty acid having 12 to 24 carbon atoms.
[0051] The ester compound may in particular be a monoester of an alkylene glycol having 2 to 6 carbon atoms and a fatty acid having 15 to 24 carbon atoms. The alkylene glycol may be, for example, ethylene glycol, propylene glycol, diethylene glycol, etc. The fatty acid having 15 to 24 carbon atoms may be saturated or unsaturated, for example, stearic acid, behenic acid, etc.
[0052] Specific examples of the ester compound include propylene glycol monostearate and propylene glycol monobehenate.
[0053] The content of the ester compound in the transparent moisture-absorbing layer is from 2.0% to 15% by mass, based on the total mass of the transparent moisture-absorbing layer, and may be from 2.5% to 3.0% by mass, or from 5.0% to 12% by mass, from 10% to 8.0% by mass, or from 6.0% to 6.0% by mass. For example, the content of the ester compound may be from 2.5% to 12% by mass, or from 3.0% to 10% by mass.
[0054] <Skin layer> The first and second skin layers are layers laminated on the surfaces of the moisture absorbing layer, and each of these skin layers contains a cyclic olefin polymer.
[0055] The content of the cyclic olefin polymer is preferably 10% by mass or more, 20% by mass or more, or 30% by mass or more, based on the mass of the skin layer, from the viewpoint of suppressing deactivation of the moisture absorbent, and is preferably 100% by mass, 90% by mass or less, 80% by mass or less, 70% by mass or less, 60% by mass or less, 50% by mass or less, or 40% by mass or less, from the viewpoint of improving moisture absorption.
[0056] The thickness of the first and second skin layers can be 1 μm or more, 3 μm or more, 5 μm or more, 7 μm or more, or 10 μm or more, and can be 300 μm or less, 200 μm or less, 100 μm or less, 80 μm or less, 50 μm or less, 40 μm or less, 30 μm or less, 20 μm or less, or 15 μm or less. The thickness of the first and second skin layers can be the same or different.
[0057] (Cyclic olefin polymer) Cyclic olefin-based polymers are polymers having cyclic olefin moieties and can be cyclic olefin polymers and / or α-olefin-cyclic olefin copolymers.
[0058] In the present invention, examples of monomers constituting the cyclic olefin polymer (COP) include vinylcycloalkanes such as vinylcyclopropane, vinylcyclobutane, vinylcyclopentane, and vinylcyclohexane, and derivatives thereof; monocycloalkenes such as cyclopropene, cyclobutene, cyclopentene, cyclohexene, cycloheptene, cyclooctene, and cyclooctene, and derivatives thereof; bicyclo[2.2.1]hept-2-ene (norbornene), tricyclo[4.3.0 ... 2,5 ]dec-3-ene, tetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene, pentacyclo[6.5.1.1 3,6 .0 2,7 .0 9,13 ]Pentadec-4-ene, Pentacyclo[7.4.0.1 2,5 .1 9,12 .0 8,13 ]Pentadec-3-ene, Pentacyclo[8.4.0.1 2,5 .1 9,12 .0 8,13 ]Hexadec-3-ene, Pentacyclo[6.6.1.1 3,6 .0 2,7 .0 9,14 ]Hexadec-4-ene and other polycyclic alkanes and their derivatives, and combinations thereof.
[0059] In the present invention, α-olefin-cyclic olefin copolymer (COC) means a copolymer of an α-olefin portion and a cyclic olefin portion.
[0060] In the present invention, the copolymer means a copolymer composed of two or more kinds of monomers.
[0061] Examples of the α-olefin moiety include ethylene, propylene, 1-butene, 1-pentene, 4-methyl-pentene, 3-methyl-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, and the like, as well as combinations thereof.
[0062] Cyclic olefin moieties include the monomers listed for the cyclic olefin polymers.
[0063] In the olefin-cyclic olefin copolymer, the structural units derived from the α-olefin portion can be 10 mol% or more, 20 mol% or more, 30 mol% or more, 40 mol% or more, or 50 mol% or more, and can be 95 mol% or less, 90 mol% or less, 80 mol% or less, 70 mol% or less, or 60 mol% or less.
[0064] <Laminate for blister container> As shown in FIG. 2, the laminate 100 for blister containers is A transparent barrier substrate layer 20, and The transparent moisture-absorbing film 10 is laminated on the transparent barrier substrate layer 20. has.
[0065] A blister container can be manufactured by forming a pocket for putting contents in the laminate for blister containers having the above-mentioned configuration. Examples of molding methods for forming the pocket include flat plate air pressure molding, plug-assisted air pressure molding, drum vacuum molding, and plug molding. Among these, the plug molding method using a cylindrical rod (plug material) with a rounded tip made of ultra-high molecular weight polyethylene resin with a viscosity average molecular weight of 1,000,000 or more is preferable for forming the pocket. By using such a means, the pocket can be formed so that the skin layer side is concave.
[0066] <Transparent Barrier Substrate Layer> The transparent barrier substrate layer is a substrate having transparency and barrier properties.
[0067] The transparent barrier substrate layer may be, for example, a barrier resin layer. Examples of the resin constituting the barrier resin layer include the above-mentioned cyclic olefin polymer, ethylene-vinyl alcohol copolymer, polychlorotetrafluoroethylene (PCTFE), etc.
[0068] 2, the transparent barrier substrate layer 20 may be a layer having a transparent barrier layer 22 and a transparent substrate resin layer 24. In this case, an adhesive layer may be present between the transparent barrier layer and the transparent substrate resin layer.
[0069] (Transparent barrier layer) The transparent barrier layer may be made of a material that is transparent and can suppress the permeation of moisture, organic gases, and inorganic gases from the outside into the transparent moisture absorbing layer. Such a transparent barrier layer may be made of an inorganic vapor deposition film such as a silica vapor deposition film, an alumina vapor deposition film, or a silica-alumina binary vapor deposition film, or an organic coating film such as a polyvinylidene chloride coating film, a polychlorotetrafluoroethylene coating film, or a polyvinylidene fluoride coating film. The above-mentioned barrier resin layer may also be used as the transparent barrier layer.
[0070] When an inorganic vapor deposition film or an organic coating film is used as the transparent barrier layer, the thickness of the transparent barrier layer is preferably 100 nm or more, 200 nm or more, 300 nm or more, 500 nm or more, 700 nm or more, or 1 μm or more from the viewpoint of ensuring strength and barrier properties, and is preferably 5 μm or less, 4 μm or less, 3 μm or less, or 2 μm or less from the viewpoint of improving handleability as a blister container.
[0071] When a barrier resin layer is used as the transparent barrier layer, the thickness of the transparent barrier layer is preferably 7 μm or more, 10 μm or more, or 15 μm or more from the viewpoint of ensuring strength and barrier properties, and is preferably 45 μm or less, 40 μm or less, or 35 μm or less from the viewpoint of improving handleability as a blister container.
[0072] (Transparent base resin layer) As the transparent substrate resin layer, a thermoplastic resin having excellent impact resistance, abrasion resistance, etc., such as a polyolefin resin, a vinyl polymer, a polyester, a polyamide, etc., can be used alone or in a multi-layer structure by combining two or more kinds. This resin layer may be a stretched film or a non-stretched film. In addition, this resin layer may be present on one or both sides of the transparent barrier layer. This resin layer can protect the transparent barrier layer.
[0073] For polyolefin resins, vinyl polymers, polyesters, and polyamides, the descriptions regarding the moisture absorbing layer can be referred to.
[0074] As the transparent substrate resin layer, it is preferable to use polyvinyl chloride and / or polypropylene resins from the viewpoint of achieving both moldability and rigidity.
[0075] The thickness of the transparent substrate resin layer is preferably 10 μm or more, 20 μm or more, 30 μm or more, 50 μm or more, 70 μm or more, 100 μm or more, 120 μm or more, 150 μm or more, 180 μm or more, or 200 μm or more, from the viewpoint of providing good protection for the barrier layer, and is preferably 300 μm or less, 280 μm or less, 250 μm or less, or 220 μm or less, from the viewpoint of improving handleability as a blister container.
[0076] <Blister pack with contents> The content-filled blister pack of the present invention comprises: contents, A blister container comprising the above laminate for a blister container and having a pocket; and a lid material attached to the blister container, thereby sealing the contents. has.
[0077] The lid material may be adhered to the blister container via an adhesive layer, or may be fused to the blister container.
[0078] <Contents> The contents are the contents sealed in the pockets of the blister container. Such contents are not limited as long as they can deteriorate when exposed to the outside air, and examples of such contents include medicines, food, cosmetics, sanitary products, medical devices, medical instruments, electronic parts, etc. Furthermore, medicines include pharmaceutical preparations, cleaning agents, pesticides, reagents, etc.
[0079] The configuration of the present invention is particularly useful when the contents are preferably visually recognizable, such as pharmaceutical preparations bearing text information such as a dosing expiration date.
[0080] <Blister container> The blister container is constructed from the above-mentioned laminate for a blister container and has a pocket.
[0081] Such a blister container can be manufactured, for example, by forming a pocket for putting contents in the above-mentioned laminate for blister containers. Examples of the molding method for forming the pocket include flat plate air pressure molding, plug-assisted air pressure molding, drum vacuum molding, plug molding, etc. Among these, the plug molding method using a cylindrical rod (plug material) with a rounded tip made of ultra-high molecular weight polyethylene resin with a viscosity average molecular weight of 1,000,000 or more is preferred for forming the pocket.
[0082] <Lid material> The lid material is adhered to the blister container, thereby sealing the contents. The lid material may have, for example, a base resin layer and a barrier layer. The lid material may also have an easily peelable layer on the surface that adheres to the blister container. The lid material may or may not be transparent as a whole.
[0083] As such a lid material, for example, a commercially available lid material for press-through packages (PTP) can be used. EXAMPLES
[0084] The present invention will be specifically described with reference to examples and comparative examples, but the present invention is not limited to these.
[0085] <<Preparation of transparent moisture-absorbing film>> Example 1 A two-kind, three-layer film was produced by co-extrusion molding using a multi-layer T-die film-making machine, with the transparent skin layer, transparent moisture-absorbing layer, and transparent skin layer arranged in that order. The transparent skin layer was a resin composition obtained by dry-blending 70 parts by mass of linear low-density polyethylene (LLDPE) with 30 parts by mass of cyclic olefin copolymer (COC). The transparent moisture-absorbing layer was a resin composition prepared by melt-kneading 68 parts by mass of ethylene-vinyl acetate copolymer (EVA) (EV150, Mitsui DuPont Polychemicals Co., Ltd.), 28 parts by mass of Na-A type zeolite (nano zeolite, average particle size D50: 50 nm), and 4 parts by mass of an ester compound (propylene glycol monobehenate, HLB value 3.4) at a temperature of 160°C for 10 minutes in a Banbury mixer. The thickness of each layer was 10 μm for the transparent skin layer, 40 μm for the transparent moisture-absorbing layer, and 10 μm for the transparent skin layer.
[0086] Examples 2 to 4 and Comparative Examples 1 to 2 Films of Examples 2 to 4 and Comparative Examples 1 and 2 were produced in the same manner as in Example 1, except that the configuration of each layer was changed as shown in Table 1. The details of the substances mentioned in Table 1 are as follows: LDPE: Low density polyethylene Zeolite 4A: Molecular sieve 4A, Union Showa Co., Ltd., average particle size greater than 1 μm
[0087] "evaluation" <Inactivation rate> Each film was cut into a 10 cm square and the initial mass was measured. Then, the film was left in an environment of 23°C and 50% RH for a certain period of time, and the weight was measured again. The increase in weight was divided by the saturated moisture absorption amount to calculate the deactivation rate.
[0088] <Blocking resistance> Two pieces of the film were cut out, the skin side of each film was stacked, and 1 kg / 1 cm was applied from the top. 2 The film was pressed against the upper film with a force of 0.01 mm. The blocking resistance of the film was evaluated by observing whether the lower film was lifted when the upper film was lifted. The evaluation criteria were as follows: ○: The film did not lift. ×: The film was lifted.
[0089] Haze In order to evaluate the transparency of each of the produced films, the haze value of each was measured using a haze meter.
[0090] <Moldability> Each of the films produced was laminated to a PVC / PVDC substrate using a dry lamination adhesive to produce a laminate for blister packs. The laminate was then heated on a hot plate at 100°C or 140°C for 1 minute, and a pocket with a diameter of 13 mm and a depth of 5.25 mm was formed in the laminate using a press to produce a blister container. The evaluation criteria were as follows: ◯: No abnormal appearance such as cracks or cloudiness was observed in the pocket after molding. ×: In the pocket after molding, abnormal appearance such as cracks or cloudiness was observed, or the laminate for blister packs was broken during molding.
[0091] Table 1 shows the configurations and evaluation results of the examples and comparative examples.
[0092] [Table 1]
[0093] It can be seen from Table 1 that the films of Examples 1 to 4, in which the moisture absorbing layer contains nano zeolite and the skin layer contains a cyclic olefin polymer, had good deactivation rates, blocking resistance, and haze. In addition, the blister containers obtained using these transparent moisture absorbing films had good moldability.
[0094] In contrast, the film of Comparative Example 1, in which the skin layer did not contain a cyclic olefin polymer, had good haze but poor deactivation rate and blocking resistance.
[0095] In the film of Comparative Example 2, in which the moisture absorption layer contained zeolite 4A and the skin layer did not contain a cyclic olefin polymer, the deactivation rate and blocking resistance were good, but the haze was not good. [Explanation of symbols]
[0096] 10 Transparent moisture absorbing film 12 Transparent moisture absorption layer 14, 14' Skin layer 20 Transparent barrier substrate layer 22 Transparent barrier layer 24 Transparent base resin layer 100 Laminate for blister container
Claims
1. A transparent moisture absorbing layer containing a thermoplastic resin, a moisture absorbent, and an ester compound having an HLB value of 5 or less; and a first skin layer and a second skin layer laminated on the surface of the transparent moisture-absorbing layer, having the thermoplastic resin is a polyethylene-based resin containing a polar group and an ethylene unit, The particle diameter D50 of the moisture absorbent measured by a dynamic light scattering method is 1 μm or less, and The first and second skin layers each contain a cyclic olefin polymer. Transparent moisture absorbing film.
2. 2. The transparent moisture-absorbing film according to claim 1, wherein the thermoplastic resin is an ethylene-vinyl acetate copolymer.
3. 3. The transparent moisture-absorbing film according to claim 1, wherein the moisture absorbent is a zeolite having a particle diameter D50 of 300 nm or less as measured by a dynamic light scattering method.
4. 4. The transparent moisture-absorbing film according to claim 1, wherein the content of the ester compound is 2.0 to 15.0% by mass based on the total mass of the transparent moisture-absorbing layer.
5. 5. The transparent moisture-absorbing film according to claim 1, wherein the ester compound is a monoester of an alkylene glycol having from 2 to 6 carbon atoms and a fatty acid having from 15 to 24 carbon atoms.
6. A transparent barrier substrate layer, and The transparent moisture-absorbing film according to any one of claims 1 to 5, which is laminated on the transparent barrier substrate layer. A laminate for a blister container, comprising:
7. contents, A blister container comprising the laminate for a blister container according to claim 6 and having a pocket; and a lid material attached to the blister container, thereby sealing the contents. A blister pack containing the contents.
Citation Information
Patent Citations
Method of manufacturing fine zeolite
JP2011246292A
Water-absorbing resin composition and water-absorbing multilayer container
JP2012158718A
Method of manufacturing fine zeolite
JP2013049602A
Multilayer laminate and package
JP2016055639A
Light transmissive moisture absorption film and method for producing the same
JP2018100390A